The Effect of Curfew Enforcement on Health Care Provision in COVID-19 Pandemic - Ensar Durmuş; Fatih Guneysu (JURNAL INFO KESEHATAN, 2020)
The COVID-19 disease occurred in the final weeks of 2019. As part of the fight against COVID-19, countries have taken actions such as travel restrictions, suspension of border crossings and international flights, voluntary home isolation, public activities restriction, and curfews. The objective of this study is to identify the effect of curfew enforcement during the COVID-19 pandemic to determine and identify whether curfew has a positive effect on the health care workload. The number of patients admitted to Sakarya University Training and Research Hospital, their means of arrival, hospitalization-discharge, demographic characteristics were examined retrospectively for the period of curfew in April and May 2020 and the corresponding days in 2019. The significant statistical differences between the two periods were analyzed. The results of this research reveal that24.488 patients were admitted to our emergency department. Of these patients, 12813 (52.3%) were male, 11675 (47.7%) were female. The number of emergency department admissions of the pediatric age group decreased from 1822 (8.9%) to 33 patients (0.8%). Moreover, the number of patients admitted to the emergency service in the related period of 2019 was 20548 (83.9%), while this figure decreased to 3940 individuals (16.1%) during the curfew period. It was impliedthat curfew could reduce the unnecessary admissions to hospitals, the number of ambulance usage, and provide a positive contribution to the reduction in traumas, car accidents, work accidents, and forensic cases during pandemic.